HD 76920 b pinned down: A detailed analysis of the most eccentric planetary system around an evolved star. (22nd April 2021) - Bergmann, C.; Jones, M. I.; Zhao, J.; Mustill, A. J.; Brahm, R.; Torres, P.; Wittenmyer, R. A.; Gunn, F.; Pollard, K. R.; Zapata, A.; Vanzi, L.; Wang, Songhu
Abstract: We present 63 new multi-site radial velocity (RV) measurements of the K1III giant HD 76920, which was recently reported to host the most eccentric planet known to orbit an evolved star. We focused our observational efforts on the time around the predicted periastron passage and achieved near-continuous phase coverage of the corresponding RV peak. By combining our RV measurements from four different instruments with previously published ones, we confirm the highly eccentric nature of the system and find an even higher eccentricity of e=0.8782 ± 0.0025, an orbital period of 415.891^+0.043_-0.039 d, and a minimum mass of 3.13^+0.41_-0.43 M_J for the planet. The uncertainties in the orbital elements are greatly reduced, especially for the period and eccentricity. We also performed a detailed spectroscopic analysis to derive atmospheric stellar parameters, and thus the fundamental stellar parameters ( M_*, R_*, L_* ), taking into account the parallax from Gaia DR2, and independently determined the stellar mass and radius using asteroseismology. Intriguingly, at periastron, the planet comes to within 2.4 stellar radii of its host star's surface. However, we find that the planet is not currently experiencing any significant orbital decay and will not be engulfed by the stellar envelope for at least another 50–80 Myr. Finally, while we calculate a relatively high transit probability of 16%, we did not detect a transit in the TESS photometry.